2007
DOI: 10.1159/000110737
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a New α<sub>2</sub>δ Ligand PD-217014 on Visceral Hypersensitivity Induced by 2,4,6-Trinitrobenzene Sulfonic Acid in Rats

Abstract: PD-217014, a new GABA analog (1α,3α,5α-3-aminomethyl-bicyclo[3.2.0]heptane-3-acetic acid), inhibited [3H]-gabapentin binding to α2δ subunit of voltage-gated calcium channels in a concentration-dependent manner (Ki = 18 nmol/l). Oral treatment with PD-217014 significantly inhibited the visceral hypersensitivity induced by an intra-colonic injection of trinitrobenzene sulfonic acid in rats. The anti-hyperalgesic effect of PD-217014 increased in a dose-dependent manner, and reache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Modulation of Ca v 2.2 channel activity is implied in the pharmacodynamics of pain-relieving compounds, such as other Gi-coupled receptor agonists, eg, opioids, cannabinoids, neuropeptide Y, and substance P. 7,78,81,87,91 Also, the neuropathic pain analgesics gabapentin and pregabalin 28 inhibit Ca v 2.2mediated synaptic transmission. 6,88 Gabapentinoids are effective in reducing visceral pain and preventing spinal neuronal activation associated with CRD in animals 62,69,79 and have been suggested to be treatments for IBS. 11 A direct inhibitor of Ca v 2.2 channel activity, ziconotide, is currently used clinically for pain therapy, although it is limited to the intrathecal route.…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of Ca v 2.2 channel activity is implied in the pharmacodynamics of pain-relieving compounds, such as other Gi-coupled receptor agonists, eg, opioids, cannabinoids, neuropeptide Y, and substance P. 7,78,81,87,91 Also, the neuropathic pain analgesics gabapentin and pregabalin 28 inhibit Ca v 2.2mediated synaptic transmission. 6,88 Gabapentinoids are effective in reducing visceral pain and preventing spinal neuronal activation associated with CRD in animals 62,69,79 and have been suggested to be treatments for IBS. 11 A direct inhibitor of Ca v 2.2 channel activity, ziconotide, is currently used clinically for pain therapy, although it is limited to the intrathecal route.…”
Section: Discussionmentioning
confidence: 99%
“…New α 2 δ ligands are starting to appear in literature, but to date, only one of these, PD-217014, which has similar binding affinity at the α 2 δ binding site as pregabalin, has been investigated in an animal model of visceral hypersensitivity (Ohashi et al, 2008). In the TNBS model described previously, oral dosing of PD-217014 (3–100 mg/kg) dose-dependently inhibited the reduction in colonic nociception threshold observed 7 days after TNBS administration.…”
Section: Pre-clinical Models Of Gi Sensation and Motilitymentioning
confidence: 99%
“…This study identified reduced presynaptic Ca 2+ channels and smaller auditory nerve fiber terminals synapsing on cochlear nucleus bushy cells to be associated with a specific hearing impairment resulting from the loss of a 2 d-3. Other related compounds include 4-methylpregabalin and similar molecules (Ohashi et al, 2008;Corrigan et al, 2009). These compounds were not designed as drugs with a 2 d binding in mind; rather, they were intended to increase GABA A receptor activation.…”
mentioning
confidence: 99%